2017
DOI: 10.1137/15m1044679
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Ensemble Propagation for Improving Performance, Portability, and Scalability of Uncertainty Quantification on Emerging Computational Architectures

Abstract: Quantifying simulation uncertainties is a critical component of rigorous predictive simulation. A key component of this is forward propagation of uncertainties in simulation input data to output quantities of interest. Typical approaches involve repeated sampling of the simulation over the uncertain input data, and can require numerous samples when accurately propagating uncertainties from large numbers of sources. Often simulation processes from sample to sample are similar and much of the data generated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Conceptually our array wrapper is similar to SIMD data types studied by others [17,14,31,15,24], which have been used to achieve some form of outer-loop vectorization by blocking the outer loop based on the architecture's vector width and moving the vector loop to an innermost loop encapsulated by overloaded operators iterating over a statically-sized array. Furthermore, these implementations have focused exclusively on vector CPU/Phi architectures with compile-time fixed array lengths.…”
Section: Implementation Using Kokkosmentioning
confidence: 99%
“…Conceptually our array wrapper is similar to SIMD data types studied by others [17,14,31,15,24], which have been used to achieve some form of outer-loop vectorization by blocking the outer loop based on the architecture's vector width and moving the vector loop to an innermost loop encapsulated by overloaded operators iterating over a statically-sized array. Furthermore, these implementations have focused exclusively on vector CPU/Phi architectures with compile-time fixed array lengths.…”
Section: Implementation Using Kokkosmentioning
confidence: 99%
“…To our knowledge, such an approach has not yet been explored in detail: Only in [21,22] a synthetic output of interest from the computer model is used to predict the number of internal iterations one run takes. With this information, the authors group the runs with similar iterations together to an so called ensemble group.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we have recently undertaken work that further attempts to reduce computational cost for sampling-based UQ methods by reducing the cost of the evaluation of each sample. In particular we have shown [45] that performance can be substantially improved when multiple samples are propagated through a computational simulation together, a technique we call embedded ensemble propagation. In [45] ensembles of samples were propagated through a canonical model of a stochastic isotropic diffusion equation with uncertain diffusion coefficient by replacing all sample-dependent scalars within the simulation code 1 with small arrays.…”
mentioning
confidence: 99%
“…In particular we have shown [45] that performance can be substantially improved when multiple samples are propagated through a computational simulation together, a technique we call embedded ensemble propagation. In [45] ensembles of samples were propagated through a canonical model of a stochastic isotropic diffusion equation with uncertain diffusion coefficient by replacing all sample-dependent scalars within the simulation code 1 with small arrays. It was found that the cost of assembling and solving the resulting linear equations of the ensemble system was substantially smaller compared to assembling and solving each system sequentially when implemented on a variety of contemporary and emerging computational architectures for several reasons:…”
mentioning
confidence: 99%
See 1 more Smart Citation